Exploring Women’s Transition into and Participation in Formal Paid Employment: Case Studies in Regional Indonesia - Prihatiningtyastuti, Endah (Curtin University, 2022)
This study examines women’s access to decent work in a regional Indonesian context. This study employ structuration theory and a feminist policy analysis framework. Case study analysis was undertaken that included interviews with 40 women workers and key policy stakeholders in two rural districts of Jatva. The findings indicate that women’s transitioning into formal employment and decent work is limited by structural and cultural barriers to participation.